2001
DOI: 10.1055/s-2001-15838
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous translymphatic thoracic duct embolization for treatment of chylothorax

Abstract: Summary. A modified technique for transabdominal, translymphatic occlusion of the thoracic duct is described. During unilateral lymphangiography an abdominal lymph vessel was punctured with a fine needle under fluoroscopic guidance, and a 4 French access to the lymph system established. The thoracic duct was successfully embolized with coils and tissue adhesive in a patient with postoperative high output chylothorax. Chylous drainage immediately decreased after the intervention, the intercostal drain could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…13,18 Since then, several case reports and retrospective case series have been published. 14,[19][20][21]…”
mentioning
confidence: 99%
“…13,18 Since then, several case reports and retrospective case series have been published. 14,[19][20][21]…”
mentioning
confidence: 99%
“…The first report describing percutaneous treatment of chyle leak with catheterization of the cisterna chyli in humans was published by Cope [6] in 1998. In the following years, his experience was replicated by other authors [2,3,5,18].…”
Section: Discussionmentioning
confidence: 67%
“…We found five case series and three case reports evaluating percutaneous treatment for chyle leak [2][3][4][5][6][7][8][9]. Three of the case series were from the same institution [6][7][8], and only the most comprehensive paper was included in our analysis [7].…”
Section: Resultsmentioning
confidence: 99%
“…4 Since that publication, several authors have reported their results with this technique. [15][16][17][18][19] The technique has been extended to pediatric patients who have been successfully treated for chylothorax post open heart operations in the first 6 months of life. 20 Most recently, traumatic lacerations of the cysterna chyli have been successfully treated using multiple embolizations.…”
Section: Commentsmentioning
confidence: 99%